PENGGUNAAN MEDIA MIND MAP DENGAN APLIKASI PREZI UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA - Chamelia Putri; Retna Ngesti (Economic Education, University of Jember, 2016)
This research in order to increase student’s learning activities and values in class VIID MTs Al-Badri in topic social organization using medium Mind Map improved with Prezi features. This research is kind of classroom action research (CAR) that is designed in two cycles and each cycle consists of four phases e.g planning, action, observation, and reflection. Subjects of this research are student of grade VIID that are 33 female in number. Methods of collecting data that is used in this research are observations, interview, tests and documents. Analysis of activities data obtained from the student activity observation by observer when the teacher do the corrective actions in class, and analysis of student learning values obtained from test scores of students daily tests. This research shows that medium use Mind Map improved with Prezi feature in learning process can increase students' learning activities where student with less active category (total score: 352) become more active with total score 478 in cycle 1 and become very active category in cycle 2 with total score 555. This condition also happen in student learning values where the percentage of students who scored above the KKM before the action by 15%, and after the implementation of the first cycle increased to 36% and in cycle 2 until 76%. Based on the data analysis can be seen that by using media Mind Map improved with Prezi feature can increase student’s activities and student’s learning values.